Abrogation of Endogenous Glycolipid Antigen Presentation on Myelin-Laden Macrophages by D-Sphingosine Ameliorates the Pathogenesis of Experimental Autoimmune Encephalomyelitis - Ban, Yi; Dong, Wenjuan; Zhang, Lixing; Zhou, Tian; Altiti, Ahmad S.; Ali, Khaleel; Mootoo, David R.; Blaho, Victoria A.; Hla, Timothy; Ren, Yi; Ma, Xiaojing (Frontiers in Immunology, 2019)
Background: Although myelin is composed of mostly lipids, the pathological role of myelin lipids in demyelinating diseases remains elusive. The principal lipid of the myelin sheath is β-galactosylceramide (β-Galcer). Its α-anomer (α-Galcer) has been demonstrated to be antigenically presented by macrophages via CD1d, a MHC class I-like molecule. Myelin, which is mostly composed of β-Galcer, has been long considered as an immunologically-inert neuron insulator, because the antigen-binding cleft of CD1d is highly α-form-restricted. Results: Here, we report that CD1d-mediated antigenic presentation of myelin-derived galactosylceramide (Mye-GalCer) by macrophages contributed significantly to the progression of experimental autoimmune encephalomyelitis (EAE). Surprisingly, this presentation was recognizable by α-Galcer:CD1d-specific antibody (clone L363), but incapable of triggering expansion of iNKT cells and production of iNKT signature cytokines (IFNγ and IL-4). Likewise, a synthesized analog of Mye-Galcer, fluorinated α-C-GalCer (AA2), while being efficiently presented via CD1d on macrophages, failed to stimulate production of IFNγ and IL-4. However, AA2 significantly exacerbated EAE progression. Further analyses revealed that the antigenic presentations of both Mye-GalCer and its analog (AA2) in α-form via CD1d promoted IL-17 production from T cells, leading to elevated levels of IL-17 in EAE spinal cords and sera. The IL-17 neutralizing antibody significantly reduced the severity of EAE symptoms in AA2-treated mice. Furthermore, D-sphingosine, a lipid possessing the same hydrophobic base as ceramide but without a carbohydrate residue, efficiently blocked this glycolipid antigen presentation both in vitro and in spinal cords of EAE mice, and significantly decreased IL-17 and ameliorated the pathological symptoms. Conclusion: Our findings reveal a novel pathway from the presentation of Mye-GalCer to IL-17 production, and highlight the promising therapeutic potential of D-sphingosine for the human disorder of multiple sclerosis.